2021
DOI: 10.1371/journal.pntd.0009101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IRS: Four-years of entomological surveillance of the Indian Visceral Leishmaniases elimination programme

Abstract: Background In 2005, Bangladesh, India and Nepal agreed to eliminate visceral leishmaniasis (VL) as a public health problem. The approach to this was through improved case detection and treatment, and controlling transmission by the sand fly vector Phlebotomus argentipes, with indoor residual spraying (IRS) of insecticide. Initially, India applied DDT with stirrup pumps for IRS, however, this did not reduce transmission. After 2015 onwards, the pyrethroid alpha-cypermethrin was applied with compression pumps, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 33 publications
2
9
2
Order By: Relevance
“…The inability to detect L. donovani DNA in P. argentipes in the Saran villages is surprising considering that VL and PKDL cases were reported on the KAMIS system in months leading up to and after when the work was performed. However, similar low infections rates in P. argentipes were also reported in eight VL sentinel sites undergoing routine entomological and IRS surveillance in three VL endemic States in India (27). Of 14,775 P. argentipes females tested, L. donovani DNA was detected in only four females collected in the district of East Champaran, Bihar (3/991 and 1/704 females collected 2017 and 2018, respectively).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The inability to detect L. donovani DNA in P. argentipes in the Saran villages is surprising considering that VL and PKDL cases were reported on the KAMIS system in months leading up to and after when the work was performed. However, similar low infections rates in P. argentipes were also reported in eight VL sentinel sites undergoing routine entomological and IRS surveillance in three VL endemic States in India (27). Of 14,775 P. argentipes females tested, L. donovani DNA was detected in only four females collected in the district of East Champaran, Bihar (3/991 and 1/704 females collected 2017 and 2018, respectively).…”
Section: Discussionsupporting
confidence: 67%
“…argentipes females/trap night found in a previous study performed in Saran, but higher than the mean capture rate of 2.0 P. argentipes females/trap night reported in Muzaffarpur, Bihar, another VL endemic district bordering Saran (11,21) and in other sentinel sites in India where, even during the June-September peak, densities of P. argentipes females/trap night declined from 2014-2019 (27).…”
Section: Collection Methods Comparison Studycontrasting
confidence: 65%
See 1 more Smart Citation
“…62 Another source of concern in terms of quality IRS is logistics. 51,55 Due to limited coverage, a suboptimal or defective spray may raise the cost of the programme and, as a result, the usage of insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that IRS has been the mainstay for the elimination of Kala-azar and DDT has been the insecticide of choice, IRS has been severely harmed due to a lack of proper monitoring and evaluation tools, 6,31,37,53,54 whilst a four-year assessment of IRS coverage revealed that while there has been progress, much more improvement is needed. 55 In 2009, TDR/WHO and German collaboration (BMZ/GIZ) developed an IRS toolkit for use in a multi-country study in India, Bangladesh, and Nepal. This tool set for IRS quality assurance included a number of indicators.…”
Section: Figure 1a Schematic Diagram For Reason Of Development Of Res...mentioning
confidence: 99%